(untitled) (Bangladesh Journal of Botany, 2024)
This study aimed to explore the geometric morphological variation characteristics of the leaves of the understory plant Loropetalum chinense under different competitive pressures. Specifically, the leaf morphological indices were calculated, and multiple comparison analysis and Fisher linear discriminant model were employed to decipher the morphological variability based on contour outlines. The results revealed that the leaf morphological indices exhibited significant differences among various sample plots. The lower stand density and DBH (diameter at breast height) facilitated more water and air exchange and led to a rounded leaf shape. The results provided a theoretical basis for the study of response of leaf morphological evolution to forest competition. Bangladesh J. Bot. 53(3): 681-687, 2024 (September) Special